A Review of Various Steganography Techniques in Cloud Computing - Akeel Awadh, Wid; Salah Hashim, Ali; Khalaf Hamoud, Alaa (University of Thi-Qar Journal of Science, 2019)
One of the latest trends in IT sector is cloud computing. It develops the capabilities of organizations dynamically without training new employees, obtaining new software licenses or investing in infrastructure. At present, user keeps and share a high amount of data on cloud, and hence, the security of cloud computing is necessary so that there is no threat to any of the user’s data. Steganography is becoming a standard practice for both cloud users and cloud service providers as a mechanism against unauthorized surveillance. Steganography refers to writing hidden messages in a way that only the sender and receiver have the ability to safely know and transfer the hidden information in the means of communications. The aim of this paper is to provide an overview of steganography in cloud computing and compare various studies on the basis of technique selection, carrier formats, payload capacity and embedding algorithm to open important research directions.